أحاديث الفتن والملاحم الواردة في كتاب "التذكرة" للإمام القرطبي : دراسة تخريجية - Nur Husna binti Mazlan (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research studies the fifty ahadith that are mentioned in Book of Al-Tadhkirah by Imam al-Qurtubi beginning chapter “The Destruction of Makkah and Madinah” until chapter “Signs of the Resurrection”. This research highlights the effort of Imam al-Qurtubi in compiling ahadith on the destruction of Makkah and Madinah, the appearance of the Mahdi and the signs of resurrection. The methodology used was quantitative data collection of hadith marfu' recorded in “Al-Tadhkirah – other than documented in the six books (kutub as-sittah) -”. These ahadith were then categorized based on the level of validity after studying the matn or text of hadith and sanad or chains of hadith narrators. From the research, it was found that there are four ahadith on destruction of Makkah and Madinah; one hadith is Sahih li Dhatihi and one hadith is Sahih li Ghayrihi and two ahadith are left ungraded due to the unavailability of their chains of narration and sources. Meanwhile, there are eleven ahadith on appearance of Mahdi; one Sahih li Dhatihi, two Sahih li Dhatihi, two Da'if, one Daif Jiddan, five Mawdu' and one hadith left ungraded due to the unavailability of their chains of narration and sources. For ahadith on signs of resurrection, four ahadith are Sahih li Dhatihi, three ahadith are Sahih li Ghayrihi, eight ahadith are Hasan li Dhatihi, four ahadith are Hasan li Ghayrihi, seven ahadith are Da'if, five ahadith are Da'if Jiddan, one Mawdu', and three ahadith were left ungraded due to the unavailability of their chains of narration and sources.